Development of air conditioner split R32 trainer learning media in cooling and air conditioning engineering courses - Fitria Wahyu Ningsih; Ilham Akbar Darmawan; Mohammad Fatkhurrokhman (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study aims to develop learning media for AC Split R32 in the subject of refrigeration and air conditioning engineering. The method used Research and Development (R&D), the model of research used is Successive Approximation Models 1 (SAM). The model goes through iteration 1 (Evaluate 1, Design 1, Develop 1), iteration 2 (Evaluate 2, Design 2, Develop 2), and iteration 3 (Evaluate 3, and product implementation). The data collection method uses instruments in the form of observations, interviews, literature studies, and questionnaires that use a Likert scale for measurement the instrument. Based on the research analysis results, media trainers get an average of 76 in the